Culture and otherness represented in science fiction: confluences - Pereira, Ana Alice da Silva (Revista de Letras, 2018)
Science fiction, as a part of fantastic literature line, deals with aspects of a future brought to the present through narratives that embody technologies and knowledge that are not part of the scientific reach of the period. Even with a certain “unreality”, this approach allows the emergency of questions related to the contemporary way of living. Given that, the purpose of this article is to discuss how science fiction enables to know about man nowadays and the way he relates to others. In order to do that, there were sought theoretical contributions from literary theory, social sciences and psychoanalysis. The following questions are highlighted among the presented: the constant vigilance and monitoring; medicalization of emotions, new approaches to alterity and its difficulties; the obsolescence of the body and transformations made possible by science. Finally, art, and literature specially, is set as a possibility to demonstrate the anxiety and disquiet in face of an uncertain for coming.